Overviewing Asynchronous Motor Boost Constant Power Control Technology - GOU Jun-shan; HUANG Xin-yu (机车电传动)
The less using boost constant power conditions of AC asynchronous motor operation was described. Application, character and merit of boost constant power control were discussed, and some practical examples were provided for reference to motor and system designing.